Big data and computational intelligence in networking - Wu, Yulei; Hu, Fei 1972-; Min, Geyong; Zomaya, Albert Y. (CRC Press, 2018)
This book presents state-of-the-art solutions to the theoretical and practical challenges stemming from the leverage of big data and its computational intelligence in supporting smart network operation, management, and optimization. In particular, the technical focus covers the comprehensive understanding of network big data, efficient collection and management of network big data, distributed and scalable online analytics for network big data, and emerging applications of network big data for computational intelligence